Mediator Role of Quality Work Life in Relationship Between Perception of Job Embeddedness and Intention to Leave Work in Nurses: A Cross-Sectional Study - Hanife Tiryaki Şen; Ece Uysal Kasap; Fatma Demirkaya (Verimlilik Dergisi)
Purpose: The aim of the study is to examine the relationships between the perception of “job embeddedness”, “quality of work life” and “intention to leave” among nurses and to determine the effect of “quality of work life” on the relationship between the perception of “job embeddedness” and “intention to leave”.Methodology: This study was conducted between June and August 2024. It has a cross-sectional design. 244 nurses working in a public hospital in Istanbul were included in the study by convenience sampling method. Data were collected using scales regarding "job embeddedness", "quality of work life" and "intention to leave" perceptions. IBM SPSS 28.0 Hayes' PROCESS macro was used for data analysis.Findings: “Quality of work life” among nurses mediates the effect of the perception of “job embeddedness” on “intention to leave”. The findings provide an important perspective on the determinants of “intention to leave” among clinical nurses.Originality: More studies are needed to determine the factors that will enable nurses to stay in their jobs. Studies have largely focused on nursing specialty groups (intensive care, infection, emergency nurses, primary care, etc.), with a few studies focusing on general clinical nurses. Although studies have examined the relationship between perception of job embeddedness, quality of work life, and intention to leave, no study has been found that has examined the causal relationship of these three variables among clinical nurses.